(Un)Expected Contemporary Public Space - Valeria Cocco (Bollettino della Società Geografica Italiana, 2021)
The paper analyzes the contemporary concept of public space. It focuses the attention on the transformation of the traditional concept of public space into the idea of an alternative public space (i.e. collective space, open space, hybrid space, etc.). The methodology adopted for research purposes is mainly empirical. The case study analyzes the MAXXI museum in Rome, that shows a spontaneous birth of a (un) expected form of public space in the museum pole. This phenomenon expresses a clear need of an alternative, safe, cultural, innovative, contemporary, public space.